Diet composition and neighboring prey community of the Phuping newt (Tylototriton uyenoi) in Maesa–Kogma Biosphere Reserve, Chiang Mai Province, northern Thailand - THANSUDA DOWWIANGKAN; YODCHAIY CHUAYNKERN; PONGRAT DUMRONGROJWATTANA; Prateep Duengkae (Society for Indonesian Biodiversity, 2020)
Abstract. Dowwiangkan T, Chuaynkern Y, Dumrongrojwattana P, Duengkae P. 2020. Diet composition and neighboring prey community of the Phuping newt (Tylototriton uyenoi) in Maesa–Kogma Biosphere Reserve, Chiang Mai Province, northern Thailand. Biodiversitas 21: 4515-4523. The present work reports the comparison of fecal pellet prey composition of Tylototriton uyenoi from Maesa-Kogma Biosphere Reserve (Chiang Mai Province, northern Thailand) based on an analysis of its fecal pellets. Males of T. uyenoi consumed more diverse prey than those of females (53 groups of prey versus 14 groups). The analysis reveals a diverse diet of Arthropoda (Insecta, Arachnida, Diplopoda, Chilopoda, and Malacostraca), Mollusca (Gastropoda), Chordata, and conspecific eggs. Partial remnants of plant materials were also found in the pellets. The percentage frequency of prey occurrence was higher in Formicidae (21.34), Lymnaeidae (17.39), unknown snails (10.67), and Blattidae (9.881). The percentage of the relative number of preys was higher in Lymnaeidae (41.02) and Formicidae (17.17). The volumetric prey percentage was higher in Lymnaeidae (30.78), Paradoxosomatidae (19.14), and unknown snails (12.71). The index of relative importance was higher in Lymnaeidae (1,248.62), Formicidae (376.972), unknown snails (188.275), and Paradoxosomatidae (166.433). The percentage of IRI was higher in Lymnaeidae (57.128) and Formicidae (17.248). The Spearman rank coefficient (95% confidence interval test) showed a significant positive correlation (p<0.05) between prey volume and number and SVL.